An isogeometric-symplectic coupling approach for fracture analysis of magnetoelectroelastic bimaterials with crack terminating at the interface. (July 2019) - Zhou, Zhenhuan; Yu, Xiong; Yang, Zhenting; Xu, Wang; Lim, C.W.; Xu, Xinsheng
Highlights: A new enhanced IGA approach is proposed for fracture analysis of MEE bimaterials. Cracks terminating at the interface are considered. Explicit solutions near the crack tip are obtained. Intensity coefficients are defined to evaluate the fracture behaviors of the crack. Cracked MEE bimaterials with single missing corner defect are considered. Abstract: A new and novel approach that capitalizes the advantages of isogeometric analysis (IGA) and symplectic method is proposed for the mode III fracture analysis of magnetoelectroelastic bimaterials with crack terminating at the interface. In this new approach, IGA is adopted for discretizing the overall physical domain and the analytical symplectic eigenfunctions are applied in the singular field near the crack tip. New explicit expressions for singular physical field variables are derived and new intensity coefficients are introduced and determined. The physical consequences and engineering fracture implications of this innovative coupled isogeometric-symplectic approach are fully described in a few practical, numerical examples.